1983
DOI: 10.4141/cjas83-069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Bicarbonate on Nitrogen Utilization and Feed Intake by Lambs

Abstract: Psrr-lrp, L. E. 1983

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The apparent digestibility coefficients of DM did not differ significantly among groups and ranged from 29 (I) to 40% (III) in the forestomachs, while from 22 (II, III) to 28% (I) in the small intestine. Phillipson (1983), Mess et al (1985) and Leontowicz et al (1993) did not find any effect of Na and/or Ca (Leontowicz et al, 1994) on the apparent digestibility of DM or OM.…”
Section: Discussionmentioning
confidence: 96%
“…The apparent digestibility coefficients of DM did not differ significantly among groups and ranged from 29 (I) to 40% (III) in the forestomachs, while from 22 (II, III) to 28% (I) in the small intestine. Phillipson (1983), Mess et al (1985) and Leontowicz et al (1993) did not find any effect of Na and/or Ca (Leontowicz et al, 1994) on the apparent digestibility of DM or OM.…”
Section: Discussionmentioning
confidence: 96%
“…These conditions were created in order to maximize any potential benefit of NaHCO, upon nitrogen balance (Phillip 1983 lambs (Phillip 1983;Asplund et al 1980 Support for a detrimental effect of NaHCO, on nitrogen balance can be adduced from studies by Mees et al (1985). These workers found that NaHCO.…”
Section: Resultsmentioning
confidence: 99%
“…been conflicting responses in N balance when NaHCO 3 was added to concentrate or silage diets and offered to cattle and sheep (Thomas and Wilkinson 1975;Phillip 1983;Mees et al 1985). In the study with calves fed corn silage, Thomas and Wilkinson (1975) reported that the addition NaHCO 3 to neutralize silage acidity had no effect on N retention.…”
Section: Nitrogen Retention and Acid-base Balancementioning
confidence: 99%
“…In the study with calves fed corn silage, Thomas and Wilkinson (1975) reported that the addition NaHCO 3 to neutralize silage acidity had no effect on N retention. However, Phillip (1983) reported that the addition of 4% NaHCO 3 to a diet based on barley and corn silage tended to improve N balance in lambs, particularly with a low protein diet. Mees et al (1985) observed no effect of NaHCO 3 (3.5%) on N balance in lambs fed a low or high protein diet; there was, however, significant reduction in urinary N excretion at the low protein intake.…”
Section: Nitrogen Retention and Acid-base Balancementioning
confidence: 99%
See 1 more Smart Citation